Understanding the rheology of liquid protein formulations - Domingues Goncalves, Andrea (2013)
The work described in this thesis had the main aim of understanding protein solution rheology. This was from a biopharmaceutical perspective, with account of the biophysical properties of proteins and in particular their level of aggregation. Molecular interactions influencing the rheology of a range of protein solutions were studied. Proteins were selected to relate directly to the diversity of protein types used in biopharmaceuticals. In addition, the roles of a surfactant formulation additive and synthetic amphiphilic polymers in the flow behaviour of protein solutions were studied.